Behavioural intention to adopt blockchain for a transparent and effective taxing system. (4th December 2020) - Kabir, Mohammad Rokibul
Abstract : Purpose: The purpose of this research is to assess the tax stakeholders' intention towards the adoption of blockchain technology (BT) for a transparent and effective taxing system in Bangladesh. It examines the factors influencing the behavioural intention of the users to adopt BT with a blended model built on the technology acceptance model (TAM) and self-determination theory (SDT). This research develops a prescriptive model to demonstrate how the stakeholders are interested in adopting BT for the taxing system. Design/methodology/approach: Data were obtained through a structured questionnaire from the stakeholders of the taxing system, including tax policymakers, tax commissioners, tax officers, lawyers, tax consultants and the taxpayers. Statistical analyses were performed using partial least square-structural equation modelling. Findings: Results reveal that out of the two primary TAM antecedents known as usefulness (PU) and ease of use (PEU), PU has a significant influence on the BT adoption intention. The only cognitive variable called autonomous motivation picked from SDT has a positive and significant impact on BT adoption for tax purpose as well. Finally, trust is found to be another important determinant for explaining stakeholders' intention to adopt BT for an efficient taxing system where transparency can be ensured. Research limitations/implications: The proposed model does not include any moderator though there might be a moderating effect in this regard. The variation described in the behavioural intention to adopt BT by the predictors is half of the total possible variations. Hence, the inclusion of variables such as social influence and controlled motivation could be interesting. Practical implications: This study is expected to provide valuable insights into policymaking for tax administrations to enhance the tax collection net and maintain transparency and efficiency in the taxing system. Social implications: This research has social consequences for a recently graduated developing economy such as Bangladesh, where transparency and efficiency are a matter of question. Because BT adoption can assure a convenient and favourable environment for the taxpayers upholding the principles of taxation, it can play a significant role by ensuring social justice and equity through a transparent and effective taxing system. Originality/value: This research is among the first few studies to address the issue of implementing a modern technology such as BT for an efficient taxing system from a developing country perspective. Furthermore, it combined TAM and SDT to propose a hybrid model for explaining behavioural intention to adopt an emerging technology such as blockchain, which is a new phenomenon.